2011
DOI: 10.1590/s0036-46652011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Sandfly fauna (Diptera: Psychodidae) in Parque do Sabiá complex, Uberlândia, Minas Gerais, Brazil

Abstract: SUMMARYBetween April 2003 and May 2009 phlebotomine sandflies were collected in Parque do Sabiá complex, Uberlândia municipality, Minas Gerais State, Brazil, using CDC and Shannon traps. The objective was to associate the sandfly species captured to the risk of the transmission of leishmaniasis in the municipality. The 126 captured specimens belonging to six species of phlebotomine, among which Lutzomyia (Psychodopygus) davisi (Root, 1934) predominated with 113 specimens (89.7%). The remaining captured specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…There are recent records of L . flaviscutellata in southeastern Brazil [ 27 , 28 , 53 , 95 ]. It is nearly impossible, however, to test the hypothesis of a recent expansion of L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are recent records of L . flaviscutellata in southeastern Brazil [ 27 , 28 , 53 , 95 ]. It is nearly impossible, however, to test the hypothesis of a recent expansion of L .…”
Section: Discussionmentioning
confidence: 99%
“…flaviscutellata can be found near human dwellings in rural areas. The species has been recently captured in peridomestic areas outside the Amazon forest [ 28 , 32 , 97 ] and even in peri-urban areas [ 29 , 30 , 95 , 98 ]. The ability of L .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified the presence of phlebotomines responsible for the leishmaniasis transmission on the banks of Araguari river basin (LEMOS;LIMA, 2005;PAULA et al, 2013), in the urban area of Uberlândia (PAULA et al, 2008) and in the Sabiá Park, in Uberlândia. (RODRIGUES et al, 2011). Since 1992 there is no record of human leishmaniasis cases occurred in Triângulo Mineiro region and it is essential to know the epidemiological profile of the disease, as it makes possible to identify needs and propose solutions to problems, leading to health actions.…”
Section: Introductionmentioning
confidence: 99%
“…whitmani was the second most abundant species in this study. Research carried out in several areas of Brazil described it as one of the few species of high adaptability to different environmental conditions, both climatic variations and variations in vegetation 26,29,36,37,38 .…”
mentioning
confidence: 99%